Valuing patients’ high unmet need to drive innovative therapies for inherited retinal degenerations: insights from the RIWC 2024 workshop on value - Paudel, Nabin; Daly, Avril (Frontiers in Medicine, 2025)
The importance of patient involvement in the therapeutic development ecosystem is being increasingly recognized, however not all stakeholders are fully aware of the unique perspective that patients can bring to these platforms. In this perspective article that is based on a workshop organized at the Retina International World Congress (RIWC) in Dublin in June 2024, we discuss the interpretation of value from patient’s perspective, challenges in the development of innovative medicines such as cell and gene therapies for Inherited Retinal Degenerations, the resources required to bring a drug to market, and the need to incorporate patient voice throughout the drug development pathway from pre-clinical studies to clinical trial designs, regulatory and health technology assessments decisions. We hope that this article will increase awareness among all relevant stakeholders including patients, clinicians, scientists, developers, regulators, decision makers and industry representatives on the importance of involving patients in the developmental lifecycle of novel therapies so that therapies are developed that make a meaningful improvement in patients’ lives.